Studi Kasus: Penggunaan Integrasi Cognitive Behavior Therapy (CBT) dan Expressive Writing pada Individu dengan Persistent Complex Bereavement Disorder (PCBD) - Agung Rachmadi; Elizabeth Kristi Poerwandari (Jurnal Ilmu Perilaku, 2020)
Cognitive-behavior therapy (CBT) is known as strong evidence-based therapy used in handling various psychological complaints experienced by individuals. In addition, expressive writing is also known as an effective approach given to individuals who experience painful events and cause severe distress. One significant life event that can cause distress is the death of the closest person, known as grieving. Grieving becomes a nuisance when it causes an intense and prolonged sadness and manifested in daily functioning problems of the individual. This is known as persistent complex bereavement disorder (PCBD). This single case study study aimed to explain the use of CBT integrated with expressive writing in dealing with PCBD during five meeting sessions. Through intervention CBT and expressive writing, R, who was initially confused why she always feels sad for no reason, had no interest in activity, and felt lost her direction toward life, began to be able to identify and regulate her emotions, could return to engage to her daily activities, and foster interest in finding work again. In addition, R began to have an insight that she needed to regulate grieving which she had been avoiding. Keywords: CBT, Expressive Writing, Persistent Complex Bereavement Disorder